Drosophila lipin interacts with insulin and TOR signaling pathways in the control of growth and lipid metabolism - Schmitt, Sandra; Ugrankar, Rupali; Greene, Stephanie E.; Prajapati, Meenakshi; Lehmann, Michael (Journal of cell science, 2015)
Lipin proteins have key functions in lipid metabolism, acting as both phosphatidate phosphatases (PAPs) and nuclear regulators of gene expression. We show that the insulin and TORC1 pathways independently control functions of Drosophila dLipin. Reduced signaling through the insulin receptor strongly enhances defects caused by dLipin deficiency in fat body development, whereas reduced signaling through TORC1 leads to translocation of dLipin into the nucleus. Reduced expression of dLipin results in decreased signaling through the insulin receptor-controlled PI3K/Akt pathway and increased hemolymph sugar levels. Consistent with this, downregulation of dLipin in fat body cell clones causes a strong growth defect. The PAP, but not the nuclear activity of dLipin is required for normal insulin pathway activity. Reduction of other enzymes of the glycerol-3 phosphate pathway similarly affects insulin pathway activity, suggesting an effect mediated by one or more metabolites associated with the pathway. Together, our data show that dLipin is subject to intricate control by the insulin and TORC1 pathways and that the cellular status of dLipin impacts how fat body cells respond to signals relayed through the PI3K/Akt pathway.